The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.2214/ajr.182.3.1820803
|View full text |Cite
|
Sign up to set email alerts
|

Correlating MRI and Histologic Tumor Thickness in the Assessment of Oral Tongue Cancer

Abstract: MR images provide satisfactory accuracy for the measurement of tumor thickness and staging of oral tongue cancer. Preoperative MRI is recommended to assist in treatment planning for patients with this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
96
1
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(116 citation statements)
references
References 19 publications
8
96
1
11
Order By: Relevance
“…More recent studies have demonstrated that tumor thickness on MR imaging directly correlates with histologic thickness. [19][20][21] MR imaging thickness in patients with metastatic lymph nodes tended to be greater than that in metastases-free patients, though the difference was not significant between patients with and without metastasis. 21 Tongue carcinoma varies in the tumor shape (reductive or expansive) and in the growth pattern (endophytic or exophytic).…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…More recent studies have demonstrated that tumor thickness on MR imaging directly correlates with histologic thickness. [19][20][21] MR imaging thickness in patients with metastatic lymph nodes tended to be greater than that in metastases-free patients, though the difference was not significant between patients with and without metastasis. 21 Tongue carcinoma varies in the tumor shape (reductive or expansive) and in the growth pattern (endophytic or exophytic).…”
mentioning
confidence: 69%
“…In MR imaging, the structures of normal tongue architecture and the oral tongue carcinoma can be clearly shown, and coronal MR imaging can also be used to satisfactorily measure the thickness of oral tongue carcinoma. 19 Preda et al 21 found that tumor thickness of tongue carcinoma on MR imaging correlated directly with the histologic tumor thickness, and mean tumor thickness in patients with lymph node metastases was greater than that of those without metastases; but the difference did not reach significance in 33 patients. In our 43 patients, the tumor thickness was significantly (P Ͻ .05) associated with lymph node metastases, and the thickness was a statistically significant predictor of lymph node metastases in multivariate logistic re- gression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, multi-sliced imaging techniques should be useful and convenient. Recently, the correlation between histologic tumor thickness and magnetic resonance imaging (MRI) tumor thickness was demonstrated (Iwai et al 2002;Lam et al 2004;Preda et al 2006). Then MRI tumor thickness seems to become a candidate of occult metastatic predictor, although these studies did not reach to demonstrate the relation with MRI tumor thickness and regional metastases.…”
Section: Predictors Of Occult Metastasesmentioning
confidence: 99%
“…[12] и P. Lam и соавт. [13]. Авторы показали высокую корреляцию (0,83), а также высокую чувствительность и специфичность -96 и 54% для МРТ, 100 и 88% для КТ соответственно.…”
unclassified